G151 Transforming transition for paediatric IBD patients in northern ireland. (24th May 2017) - Little, R; Szabo, A; McLaughlin, L
Abstract : The Paediatric Gastroenterology team in Belfast has been continuously developing their service to facilitate efficient transfer of adolescent care to Adult Gastroenterology. Initially this process was by referral letter only however, in view of the increasing prevalence of Inflammatory Bowel Disease (IBD), establishing a well-structured transition clinic was essential. We sought to elucidate the level of preparedness for, and experience at, transition clinic from our adolescent attendees. We devised a questionnaire seeking information about all aspects of their management including; experience of Paediatric services, their future needs and apprehensions regarding adult care. This was distributed to all adolescent patients attending transition clinic over a six month period, which they completed anonymously. Data was then collated. Of the twenty two patients surveyed one hundred percent rated the quality of care at transition clinic as excellent or good. One hundred percent agreed they were well supported by the medical and nursing staff present. Eighty two percent of respondents agreed the clinic adequately prepared them for moving to Adult Gastroenterology care. However, only fifty percent of patients knew their medication names and doses. Thirty two percent wanted more advice regarding investigations and symptom management. Seventy five percent of respondents stated they would prefer improved online advice through social media rather than the CCUK website or local support groups. Seventy five percent of patients had ongoing dietetic and psychology input. Concern regarding continuity of these valuable services and the loss of a supportive relationship with the paediatric nurse specialist were the main perceived stressors and anxieties for our patient cohort. Over the last eight years the Paediatric Gastroenterology team has successfully established transition clinics with all five healthcare trusts across the province. Collaboration between the Paediatric and Adult Gastroenterology teams in Northern Ireland has transformed the continuity, safety and patient experience for young people with IBD transitioning between our expert services. Further work to equip adolescents with knowledge regarding their medication and symptoms, in conjunction with increased provision of allied health care professionals to adult services, will enhance wellbeing and improve clinic engagement during this challenging time.